2011
DOI: 10.1051/kmae/2011030
|View full text |Cite
|
Sign up to set email alerts
|

Additional supply of decapsulatedArtemiacysts for various periods in intensive rearing of juvenile crayfish (Pacifastacus leniusculus, Astacidae)

Abstract: Key-words: astacid crayfish, juvenile, feeding, stocking densityThe additional supply of live feeds such as Artemia remains indispensable in juvenile astacid rearing from the start of independent life. Considering that cost and work could be reduced by restricting this supply, a 100-day experiment was carried out with stage 2 Pacifastacus leniusculus to evaluate the effects of different administration periods of decapsulted Artemia cysts as supplement to a dry diet at two stocking densities. Using a bifactoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…According to the results of these studies, the researchers advised to use the live feed as supplement from the onset of external feeding to guarantee the viability of juvenile crayfish. González et al (2008), supplementing a dry diet with live Artemia nauplii in excess, obtained good results (1283 mg weight, 4459 % weight gain and 3.82 % SGR) for juvenile Pacifastacus leniusculus. González et al (2011) indicated that the juvenile crayfish (P. leniusculus) receiving decapsulted Artemia cysts up to day 50 as supplement to a dry diet showed a faster growth (averaging 13.8 mm carapace length, 610 mg weight 3.05 % day −1 SGR) at the end of the experiment.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…According to the results of these studies, the researchers advised to use the live feed as supplement from the onset of external feeding to guarantee the viability of juvenile crayfish. González et al (2008), supplementing a dry diet with live Artemia nauplii in excess, obtained good results (1283 mg weight, 4459 % weight gain and 3.82 % SGR) for juvenile Pacifastacus leniusculus. González et al (2011) indicated that the juvenile crayfish (P. leniusculus) receiving decapsulted Artemia cysts up to day 50 as supplement to a dry diet showed a faster growth (averaging 13.8 mm carapace length, 610 mg weight 3.05 % day −1 SGR) at the end of the experiment.…”
Section: Discussionmentioning
confidence: 95%
“…Zaikov et al (2000), used four different diets for A. leptodactylus during up to 1 month of age under 4 diet variants: zooplankton, feed mixture, meat and soyabean meal, and reported the best results of SGR in A. leptodactylus fed with zooplankton diet (3.56 %) and fed mixture diet (3.15 %). González et al (2008), supplementing a dry diet with live Artemia nauplii in excess, obtained 3.82 % SGR for juvenile P. leniusculus.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These include Australian crayfish species (Cherax spp. ; Jones & Ruscoe, 2000;Naranjo-Páramo, Hernandez-Llamas, & Villarreal, 2004;Rodgers, Saoud, & Rouse, 2006); American red swamp crayfish (P. clarkii; Figiel & Miller, 1995;McClain, 1995); plus astacid species such as the signal crayfish (P. leniusculus; Ahvenharju, Savolainen, Tulonen, & Ruohonen, 2005;González et al, 2011a;Harlioğlu, 2009;Ulikowski, Krzywosz, & Śmietana, 2006), and noble crayfish (Astacus astacus, Linnaeus 1758), (Keller, 1988;Pursiainen, Jarvenpaa, & Westman, 1983).…”
mentioning
confidence: 99%